2011
DOI: 10.3389/fpls.2011.00050
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolite Transporters of the Plastid Envelope: An Update

Abstract: The engulfment of a photoautotrophic cyanobacterium by a primitive mitochondria-bearing eukaryote traces back to more than 1.2 billion years ago. This single endosymbiotic event not only provided the early petroalgae with the metabolic capacity to perform oxygenic photosynthesis, but also introduced a plethora of other metabolic routes ranging from fatty acids and amino acids biosynthesis, nitrogen and sulfur assimilation to secondary compounds synthesis. This implicated the integration and coordination of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 159 publications
(227 reference statements)
1
63
0
1
Order By: Relevance
“…In addition to effects on amino acid degradation, these findings point to a role of bZIP63 in coordinating subcellular metabolism. The malate shuttle across the chloroplast envelope is essential for the transport of 2-oxoglutarate and Glu between cytosol and chloroplast (Facchinelli and Weber, 2011), and thereby automatically also affects mitochondrial metabolism. Hence, it is interesting to speculate that SnRK1 coordinates the subcellular C/N balance not only by phosphorylating NR, Suc-P synthase, or F2KP, but also via transcriptional control mediated by bZIP63 leading to allocation of organic and amino acids between multiple compartments.…”
Section: Metabolic Signals Via Regulation Of Enzymes As Targets Of Snrk1mentioning
confidence: 99%
“…In addition to effects on amino acid degradation, these findings point to a role of bZIP63 in coordinating subcellular metabolism. The malate shuttle across the chloroplast envelope is essential for the transport of 2-oxoglutarate and Glu between cytosol and chloroplast (Facchinelli and Weber, 2011), and thereby automatically also affects mitochondrial metabolism. Hence, it is interesting to speculate that SnRK1 coordinates the subcellular C/N balance not only by phosphorylating NR, Suc-P synthase, or F2KP, but also via transcriptional control mediated by bZIP63 leading to allocation of organic and amino acids between multiple compartments.…”
Section: Metabolic Signals Via Regulation Of Enzymes As Targets Of Snrk1mentioning
confidence: 99%
“…At the same time, DHAP is converted into phosphoglycerate (PGA) in the presence of TPI and GAPDH (Ikemoto et al 2003). PGA is converted into phosphoenolpyruvate (PEP) with entering into second metabolism (Facchinelli and Weber 2011). Calcium can increase the second metabolism, to produce the chlorogenic acid (Ngadze et al 2014), such as cinnamic acid and coumaric acid (Clifford et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the diverse plastid-localized antiporters of the nucleotide-sugar/triose phosphate translocator (NST) family, which are essential to mobilize different carbon compounds (e.g., phosphorylated 3-, 5-, and 6-carbon sugars) across the plastid inner membrane, evolved from a "generalist" transporter selected from the host endomembrane system to extract carbohydrates from the endosymbiont (Weber et al, 2006;Facchinelli and Weber, 2011) (Figure 1B). Interestingly, alternative solutions may have evolved to take advantage of the endosymbiont photosynthates and different membrane transporters have been recruited to translocate metabolites from the photosynthetic compartment.…”
Section: Sharing Resources With the Photosynthetic Partnermentioning
confidence: 99%
“…Other plastid-localized transporters that regulate the export and import of diverse metabolites, such as 2-oxoglutarate, glucose-6-P, ribose-5-P, pyruvate, and tetrahydrofolate, evolved from proteins encoded in the host genome. The evidence suggests that a basic set of metabolite membrane transporters has been fundamental to highjack photosynthetic endosymbionts and initiate the metabolic integration (Tyra et al, 2007;Facchinelli and Weber, 2011).…”
Section: Sharing Resources With the Photosynthetic Partnermentioning
confidence: 99%